Pengembangan Model Pembelajaran Berbasis Web Powtoon Untuk Merangsang Minat Belajar Siswa Pada Mata Pelajaran Al-Qur’an Hadits Kelas 3 MI - Naila Husna Ramadhana; Andi Prastowo (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to develop a web-based learning model so that it can provide innovation in the learning process of Al-Qur'an Hadith subjects in the Surah An-Nas material which students must memorize and can remember the meaning, so researchers want to develop web-based learning with powtoon media to provide an interesting learning experience and can provide convenience to students. The research method using research and development and the development model carried out in this study is the ADDIE model which consists of five steps, namely: analysis (analyze), design (design), development (development), implementation (implementation), evaluation (evaluation). This research was conducted at MIN Hulu Sungai Selatan II. This research provides a product in the form of animated video powtoon to be tested for feasibility by media experts, material experts, and two groups of 18 students. The results of the trial were media experts with an average score of 3.6 which was categorized as very valid, material experts with an average value of 4 and categorized as very valid, and student respondents with an average score of 3.62 in the very good category.